Peran Kepemimpinan Perempuan dengan Perspektif Gender di MIN Se-Kota Bandar Lampung - Juniasari Juniasari; Eti Hadiati; Riyuzen Praja Tuala (Universitas Negeri Malang, 2020)
Abstract: This study aims to analyze the role of female leadership from a gender perspective at Madrasah Ibtidaiyah Negeri (MIN) schools in Bandar Lampung City, focusing on their effectiveness, challenges, and contributions to advancing educational institutions. Gender stereotypes often shape perceptions of women's leadership abilities, particularly in religious-based educational environments. A qualitative descriptive approach was used in this study, employing data collection methods such as in-depth interviews, observations, and documentation. The results of the study indicate that women are capable of performing leadership roles effectively, especially in building effective communication, motivating educators, and creating an inclusive work environment. However, they also face various obstacles, such as gender stereotypes, societal expectations, and limitations in making strategic decisions. Despite these challenges, support from gender equality policies and school collaboration helps them overcome these issues. The conclusion of this study emphasizes that female leadership in MIN schools in Bandar Lampung City holds significant potential for improving the quality of education, with recommendations for strengthening gender equality policies and providing leadership training for women. This research contributes to demonstrating their effectiveness in creating an inclusive work environment, effective communication, and motivation for educators, despite facing gender stereotypes. The study recommends gender equality policies and leadership training to support women's roles in religious-based education. Keywords: Leadership, Women, Gender Perspective Abstrak: Penelitian ini bertujuan untuk menganalisis peran kepemimpinan perempuan dari perspektif gender di Madrasah Ibtidaiyah Negeri (MIN) se-Kota Bandar Lampung, dengan fokus pada efektivitas, tantangan, dan kontribusi mereka dalam memajukkan institusi pendidikan. Stereotip gender yang kerap memenuhi pandangan terhadap kemampuan perempuan dalam memimpin, khususnya di lingkungan pendidikan berbasis agama. Pendekatan deskriptif kualitatif digunakan dalam penelitian ini dengan metode pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa perempuan mampu menjalankan peran kepemimpinan dengan baik, terutama dalam membangun komunikasi efektif, memotivasi tenaga pendidik, serta menciptakan lingkungan kerja yang inklusif. Namun, mereka juga menghadapi bebagai hambatan seperti stereotip gender, ekspektasi masyarakat, dan keterbatasan dalam pengambilan keputusan strategis. Meski demikian, dukungan dari kebijakan kesetaraan gender dan kolaborasi sekolah membantu mereka mengatasi tantangan tersebut. Kesimpulan penelitian ini menegaskan bahwa kepemimpinan perempuan di MIN se-Kota Bandar Lampung memiliki potensi signifikan dalam meningkatkan kualitas pendidikan, dengan rekomendasi untuk penguatan kebijakan kesetaraan gender dan penyediaan pelatihan kepemimpinan bagi perempuan. Penelitian ini berkontribusi menunjukkan efektivitas mereka dalam menciptakan lingkungan kerja inklusif, komunikasi efektif, dan motivasi tenaga pendidik, meskipun menghadapi stereotip gender. Penelitian ini merekomendasikan kebijakan kesetaraan gender dan pelatihan kepemimpinan untuk mendukung peran perempuan dalam pendidikan berbasis agama. Kata Kunci: Kepmimpinan, Perempuan, Perspektif Gender.